Robust optimal utilization with a grid‐connected microgrid using EFO‐GBDT based controller technique with integrated converters - Padhmanabhaiyappan, S; Karthik, R; Ayyar, K. (International journal of numerical modelling, 2021)
This paper proposes the model and design of optimal utilization of grid connected Micro Grid (MG) system with Enhanced Fruit fly Optimization with Gradient Boosting Decision Tree (EFO‐GBDT) based controller technique. The integration (modeling and design) of high performance converter topology is formulated with the consideration of enhanced converter efficiency, effective implementation, source of renewable energy and reduced swapping loss. In the proposed technique the control scheme is used to consolidate the performance of both an EFO algorithm and also GBDT. In the proposed technique, the EFOA plays out an estimate method to initiate an exact control signal systems and accumulates the control signal database, an offline way of light in power variety between the source side (source of renewable energy and battery) and load side. The performance of dataset used to work as the GBDT mode for an online way and it leads to the control procedure in less performance time. In this proposed technique, an objective function is determined by the system, data subject to be an equality and inequality restrictions. The restrictions are the sources of renewable energy, power require the storage of an charged elements. A battery is implemented as source energy and it is used to permit and balance the renewable power system units and to keep running at a steady and balance output power. At that point the proposed model is performed based on MATLAB/Simulink, its working platform and the performance is assessed based on the existing techniques.